Hidden champions in Spain: The path to successful business decisions - Eva Perea Mu\~noz; Joan Ripoll-i-Alcon; Vanesa Berlanga Silvente (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
The last three decades have been a story of lost opportunities for Spanish industry to transform and improve their international competitiveness. However, there are some paradigmatic examples that violate this rule. This is the case of two Spanish companies: Hidden Champions and Brand Champions. These companies behave differently from the European and Spanish ones of similar size. They are more resilient in times of economic recession and are able to maintain and even increase their employment levels, while significantly increasing its sales and added value. This research therefore seeks to ascertain whether the Spanish hidden champions are good indicators of maturity, stability and growth of the Spanish economy; in addition to determining the reasons that have brought success and allowed these companies to recover faster than other firms. To do this, we have considered the quantitative and qualitative results collected by 75 Spanish companies to identify key management decisions. All this information is supplemented by personal interviews in order to capture more qualitative aspects about the nature of companies' management practices. The results show a typology of companies that behave differently from other companies. Managers believe that the development of close relations with customers is the first reason related to management that has led where they are today. The second is the continued development of new products and technology through innovation. Thirdly, managers consider internationalization, global approach and international alliances; whereas the fourth reason corresponds to high product specialization. Other reasons include talent management, strong leadership and company identity, quality and service, and close cooperation between managers and employees.
Keywords: C13; C21; 330; hidden champion; brand champion; global value chains (GVC); competitiveness; internationalization